Urban PM2.5 Air Pollution in Sub-Saharan Africa: A Comparative Study Between Case of Benin, Côte d'Ivoire and Senegal - (:unkn) unknown (My University, 2023)
The aim of this study is to investigate the Sub-Saharan Africa air pollution in Côte d’Ivoire, Senegal, and Benin by studying fines particles PM2.5 and to bring out their physicochemical characteristics in order to have a better knowledge on the African air pollution. Though these countries don’t share the same borders, their urban environments reveal similarities as regards higher concentrations of PM2.5. Likewise, similar repartitions of trace elements were recorded in the three countries. The ratio of specific surface area to the proportion of 2.5 µm fraction was 0.1 in the three countries. This ratio could be used to investigate African urban air. Moreover, xylene/ethylbenzene ratio was very high (11.1 in Senegal and 4.2 in Benin). This suggests a high photochemical reactivity attributable to the greatest presence of ozone in atmosphere. All results indicated that its main cause is traffic emission. Others studies in African cities are necessary in order to exclude the possible industrial dust and soil influence.
Keywords: African Research